Metode Multi-Objective Optimization on the Basis of Simple Ration Analysis Dalam Penentuan Penerima Beasiswa - Auliya Rahman Isnain (Jurnal Ilmiah Computer Science, 2023)
Scholarships provide significant benefits by opening the door to access education that previously might have been difficult to reach. The problem in this study arises from the conventional method used in the process of determining scholarship recipients. The Multi-Objective Optimization on the Basis of Simple Ration Analysis method or often known as the MOOSRA method is an innovative approach that combines two important concepts, namely multi-objective optimization and financial ratio analysis. This study aims to apply the MOOSRA method in the selection of scholarship recipients using criteria, namely the average value of report cards, parents' income, and the number of siblings. The ranking results using the MOOSRA method for scholarship recipients were obtained for rank 1, namely with a final grade of 2.17382 by Student C, rank 2 with a final grade of 1.75556 by Student B, and rank 3, namely with a final grade of 1.63415 by Student D.